The Yolanda Law, a step forward for the education for sustainable development in Argentina (Praxis Educativa, 2021)
In December 2020, the Argentinean Congress enacted Law Nº 27.592, also known as “Yolanda Law”. This norm imposes a mandatory training on environment, sustainable development and climate change for every public servant. The purpose of this article is to take this new law as a trigger to discuss the origins and current debates on environmental education, to define its relationship with human rights education, and to clarify the State obligation to guarantee that every person acquires this kind of education. Furthermore, the article will explain the main aspects of the Yolanda Law and it will highlight the most relevant speeches of the debates in both of the Chambers of the Congress. It will conclude by stating that the norm is a step forward towards achieving an environmental education for all, though we still have a long way to go.